2015 16th International Scientific Conference on Electric Power Engineering (EPE) 2015
DOI: 10.1109/epe.2015.7161143
|View full text |Cite
|
Sign up to set email alerts
|

Verification of a mutual inductance calculation between two helical coils

Abstract: This paper deals about verification process of calculation of a mutual inductance between two helical coils. Nowadays, there are many procedures how to compute mutual inductance between two coils. The main approach of proposed paper is exact specification of the formula, which may be used for the determination of the mutual inductance.First the overview of mathematical derivation is described, and final formula for computation is being determined. Based on this formula, mutual inductance for two physical helic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…In the second part of this paper we will present simulation results considering an arm for biological tissue. In the third part of the paper we described the design and measurements of small coils, with a diameter of 2,5 mm, at a distance of 10 mm, including the mandatory 2-port deembedding techniques (since coils are smaller than SMA connectors and are highly affected by them) [8][9] [10]. Finally, the last part concludes on further and current works concerning measurement deembedding in phantoms, used for modeling the muscle.…”
Section: Figure 1: the Two Cases Of Imds Rf Powering Or Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second part of this paper we will present simulation results considering an arm for biological tissue. In the third part of the paper we described the design and measurements of small coils, with a diameter of 2,5 mm, at a distance of 10 mm, including the mandatory 2-port deembedding techniques (since coils are smaller than SMA connectors and are highly affected by them) [8][9] [10]. Finally, the last part concludes on further and current works concerning measurement deembedding in phantoms, used for modeling the muscle.…”
Section: Figure 1: the Two Cases Of Imds Rf Powering Or Communicationmentioning
confidence: 99%
“…Measurements are performed with a Vector Network Analyzer and S parameters are deembedded and converted into admittance and impedance parameters under Matlab. An analytical evaluation of the self-inductance of the helical coils is given by Piri et al in [8], and reported in (2) where K(k) and E(k) are the complete elliptic integrals of the first and second kind, respectively.…”
Section: Tests With Small Coilsmentioning
confidence: 99%
“…That is, the parasitic effects are not significant and can be ignored in low frequency (LF) bands such as 100-205 kHz. Therefore, most previous researches on the mutual inductance for the WPT system have focused on the estimation of the ideal mutual inductance of two coils with respect to the alignment status [14][15][16][17][18]. For WPT systems used in the HF band such as 6.78 MHz and 13.56 MHz, the practical mutual inductances between the transmitting and receiving coils are different from the theoretical value due to the effect of the parasitic component.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid developments in cutting-edge technologies in power electronics engineering have drawn the attention of researchers to focus on inductive power transfer (IPT). The potential applications of IPT are mobile phone wireless chargers, biomedical implantable devices, contactless electric vehicle (EV) battery charging and many more [1][2][3][4]. The coupled coil structures used in the IPT system are either spiral circular or rectangular or double D in shape and these coils are resonant with inductive coupling for transfer of energy [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional methods of computing MI for various coaxial circular filaments includes Biot-Savarts Law [4], Grover's tabular data [2] etc. Recently few more methods are also reported [7,8].…”
Section: Introductionmentioning
confidence: 99%